Reflecting on Pupil Learning to Promote Social Justice: A Catholic University’s Approach to Assessment - McQuillan, Patrick J.; D’Souza, Lisa A.; Scheopner, Aubrey J.; Miller, Grant R.; Gleeson, Ann Marie; Mitchell, Kara; Enterline, Sarah; Cochran-Smith, Marilyn (Catholic Education: A Journal of Inquiry and Practice, 2009)
In contrast to current education policies that conceptualize pupil learning largely in terms of standardized exam scores, we offer an alternative view, one that conceives of pupil learning as a source of insight for pupils and teachers alike. Drawing on survey data and a qualitative study of the teacher candidate experience, we explore the following questions: In a teacher education program committed to promoting social justice, embracing an inquiry-into-practice stance, and affirming diversity by meeting the needs of diverse learners, how do teacher candidates assess pupil learning, in particular, how are their assessments influenced by these program themes? Further, how do they respond when dilemmas linked to pupil learning arise? Specifically, we focused on dilemmas two teacher candidates encountered that engendered a sense of “disequilibrium,” a feeling something was not quite right with their teaching. In turn, we consider how they responded”typically taking ownership of dilemmas and modifying their teaching, while occasionally distancing themselves from responsibility for pupil performance. To conclude, we discuss implications for teacher educators, and specifically for Catholic institutions of higher education that prepare teachers for both public and Catholic schools.